Haematological Manifestations of Covid-19 - Waziri, Aliyu Dahiru; Akor, Emmanuel Akoyi (Clinical Manifestations of Covid-19: A Multi-Disciplinary Approach, 2024)
The coronavirus SARS-CoV-2 (SARS-CoV-2) grew fast to become a global pandemic and a dreaded disease since its emergence in 2019. This work looks at the hematological manifestation and its effect on some hematological disorders. The infection through multiple pathways resulted in lymphopenia, thrombocytopenia, thrombosis and multiple unique cellular changes seen following COVID-19 infections. COVID-19 can cause severe illness and death in people with a history of sickle cell disease (SCD). Patients with thalassemia are at increased risk of developing severe illness from respiratory infections, including COVID-19, than people without SCD. Individuals diagnosed with leukemias and other hematological malignancies also demonstrated increased adverse outcomes following infection with COVID-19 infections. Vaccine-induced thrombosis (VITT), a condition that has been associated with a specific type of vaccine rapidly came to light following the widespread vaccine campaign to control the spread of the virus.